Rapid production of AZ91 Mg alloy by extrusion based additive manufacturing process. (20th October 2021) - Vishwanath, A.S.; Rane, K.; Schaper, J.; Strano, M.; Casati, R.
ABSTRACT: AZ91 magnesium alloy parts were successfully produced using a novel extrusion-based additive manufacturing process. The green parts were built in two different orientations and subjected to debinding and sintering treatments. The as-built alloy showed a heterogeneous microstructure made up of α – Mg matrix, Al8 Mn5 second phase particles, MgO layers and Mg17 Al12 continuous precipitates. After solution treatment followed by aging, Mg17 Al12 discontinuous precipitates were observed. The sintered samples showed a yield strength and ultimate tensile strength of 79 and 207 MPa, respectively, in the horizontal configuration. Analysis of the fracture surfaces revealed that a continuous network of magnesium oxide layer around the powder particles act as preferential path for crack propagation.